The students learning habit and online learning improvement during covid-19 pandemic - Yuyun Febriani; Hartini Haritani; Tri Puspita Yuliana; Puspawan Hariadi; Erma Ewisa Oktresi (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2022)
Coronavirus disease (COVID-19) has rapidly spread around the world, including in Indonesia. Some precautionary health protocol measures have been implemented due to this high infection virus, including campus class suspension. This condition made up the students learning habits has been changed. This research aimed to analyse their learning habit and educator's Improvement in online learning during this pandemic. Qualitative research by observation and questionnaires was used in this study. For observation, this research used controlling and evaluating health faculty and university instruments.  One hundred and twenty-seven responses participated in this survey. The inquiries were divided into three significant questions: language and information technology skills, duration time for learning, independent and instructional, and student participation. The research obtained that there was a decline in students learning habits during this pandemic. Thereby the educator’s Improvement, including the learning material, educational delivery method, and evaluation and assessment, must be required. Accordingly, the development and innovation of learning improvement should be continuously done.